HAK DAN KEWAJIBAN PARA PIHAK DALAM JUAL BELI TANAH YANG BELUM MEMILIKI ALAS HAK (STUDI PADA MASYARAKAT DESA HUTA RAJA, LUMBAN DOLOK DAN HAYU RAJA KECAMATAN PANYABUNGAN SELATAN KABUPATEN MANDAILING NATAL) - SOLATIAH NASUTION (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Muhd Yamin2. T. Keizerina Devi A3. Syafnil Gani Land has an important status in Customary Law because it is the only property which in spite of any condition will remain in the original state. Land title can be transferred by: Trading, Inheritance and Bequest. The selling method commonly applied by Mandailing people refers to Customary Law. This thesis discusses the frequently encountered problems in land trading among the society i.e. the land trading in which the land seller and buyer has a dispute over the buyer with good faith who has not made full payment, and the legal protection for the buyer with good faith who has paid part of the price with the agreed amount of money in advance when the seller does not acknowledge that his land has been sold. It can be concluded that the trading method performed by Mandailing people refers to the Customary Law. The preserved method is the culture that has been implemented for years by Maindailing people from generation to generation, but the long process of making the legal basis for the land so that it can become evidence that the transaction is actual, proofing that the title of the land has actually been transferred to the buyer which time limit is not made that it can cause uncertainty and dispute in the future.Keywords: Land, Trading, Customary Law